The Role of Trust in Social Entrepreneurship: A Case Study of Global Brigades. (1st March 2017) - Tack, Laura; Simon, Mark; Jiang, Ruihua Joy
Abstract : Social entrepreneurship literature acknowledges that social capital is vital to the success of social entrepreneurship efforts and trust is integral to the process of building social capital. However, there has been limited research on trust itself in social entrepreneurship literature. This article aims to begin filling this gap by utilizing a specific social entrepreneurship initiative to illustrate the role of trust in social entrepreneurship efforts. It describes the model of trust developed by Sheppard and Sherman and the social entrepreneurship initiative, Global Brigades. The article discusses the relationships between the parties involved in the initiative and applies Sheppard and Sherman's model to these relationships. It illustrates the importance of trust to social entrepreneurship efforts, as well as the need for additional research regarding social entrepreneurship and trust.